Analisa Kinerja Individu Berdasarkan Kepuasan Penggunaan E-Government di Indonesia (Studi Kasus DIKUPASI Diskopukmperindag Kota Mojokerto) - Muhammad Abdullah; Mohammad Al Hafidz; Heri Supriyanto; Muhammad Septama Prasetya; Mochamad Nurhadi; Mochammad Anang Karyawan (Jurnal Sistem Informasi Bisnis, 2024)
This study aims to determine the perceived usefulness of users of the DIKUPASI application at Diskopukmperindag in Mojokerto City by using the Usability model approach with 4 variables, namely Learnability, Flexibility, Effectiveness, and Attitude, and to analyze this usefulness on application user satisfaction and performance improvement. DIKUPASI is an institutional application that functions to monitor and update data on UKM in Mojokerto City. The research was conducted on surveyors in the City of Mojokerto using a sampling technique of 42 surveyors spread across the City of Mojokerto. The collection of research data was carried out by distributing questionnaires. Data processing is done with the SmartPLS application. The data processing that has been done shows that there are 2 hypotheses H4 and H5 obtained from the Usability model which have a significant and positive influence. Based on the results of hypothesis testing, the perception of satisfaction with the DIKUPASI application is positively and significantly influenced by user attitudes. Perceived performance improvement for DIKUPASI application users is significantly influenced positively by user satisfaction. Participation in research on the Department of Cooperatives, Small and Medium Enterprises, Industry and Trade in Mojokerto City which adopted the DIKUPASI application is necessary to pay attention to the perceptions of user attitudes so that users feel satisfied in using the application and can improve user performance. The perception of satisfaction can be created through encouragement of surveyors' willingness and how the DIKUPASI application has benefits that can help surveyors' work.